Retinoblastoma-E2F Transcription Factor Interplay Is Essential for Testicular Development and Male Fertility - Mäkelä Juho-Antti; Toppari Jorma (FRONTIERS MEDIA SA, 2022)
The retinoblastoma (RB) protein family members (pRB, p107 and p130) are key regulators of cell cycle progression, but also play crucial roles in apoptosis, and stem cell self-renewal and differentiation. RB proteins exert their effects through binding to E2F transcription factors, which are essential developmental and physiological regulators of tissue and organ homeostasis. According to the canonical view, phosphorylation of RB results in release of E2Fs and induction of genes needed for progress of the cell cycle. However, there are eight members in the E2F transcription factor family with both activator (E2F1-3a) and repressor (E2F3b-E2F8) roles, highlighting the functional diversity of RB-E2F pathway. In this review article we summarize the data showing that RB-E2F interaction is a key cell-autonomous mechanism responsible for establishment and maintenance of lifelong male fertility. We also review the expression pattern of RB proteins and E2F transcription factors in the testis and male germ cells. The available evidence supports that RB and E2F family members are widely and dynamically expressed in the testis, and they are known to have versatile roles during spermatogenesis. Knowledge of the function and significance of RB-E2F interplay for testicular development and spermatogenesis comes primarily from gene knock-out (KO) studies. Several studies conducted in Sertoli cell-specific pRB-KO mice have demonstrated that pRB-mediated inhibition of E2F3 is essential for Sertoli cell functional maturation and cell cycle exit, highlighting that RB-E2F interaction in Sertoli cells is paramount to male fertility. Similarly, ablation of either pRB or E2F1 in the germline results in progressive testicular atrophy due to germline stem cell (GSC) depletion, emphasizing the importance of proper RB-E2F interplay for germline maintenance and lifelong sperm production. In summary, while balanced RB-E2F interplay is essential for cell-autonomous maintenance of GSCs and, the pRB-E2F3 system in Sertoli cells is critical for providing GSC niche thus laying the basis for spermatogenesis.